2017
DOI: 10.1007/s00223-017-0279-y
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Tomography-Based Quantification of Cortical Porosity and Cortical Thickness at the Surgical Neck of the Humerus During Aging

Abstract: Fractures of the proximal humerus are highly related to age and osteoporotic bone remodeling. Previous studies have highlighted the cortex as a major side of the bone loss, but the microstructural changes of the humerus have not been evaluated entirely. Sixty-four (n = 64) humeri of a representative collective (18-100 years) were scanned with high-resolution peripheral quantitative computed tomography (82 µm). Bone mineral density (BMD), trabecular bone volume fraction (Tb.BV/TV), cortical thickness (Ct.Th), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Finally, microarchitectural changes of cortical bone in humeral head region could not been analyzed in the study. Some authors recently reported that cortical porosity and thickness has signi cant impact on bone loss and mechanical stability [8,9,11]. So our data were limited in predicting the risk of proximal humeral fractures.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Finally, microarchitectural changes of cortical bone in humeral head region could not been analyzed in the study. Some authors recently reported that cortical porosity and thickness has signi cant impact on bone loss and mechanical stability [8,9,11]. So our data were limited in predicting the risk of proximal humeral fractures.…”
Section: Discussionmentioning
confidence: 83%
“…Proximal humerus fragility in old age is usually attributed to age-related bone loss [4,9]. However little is known about the cortical changes in speci c regions of the humeral head.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the cortical bone thickness itself may be different depending on the individual characteristics [ 14 ]. In addition, the thickness of the cortical bone may change according to the intracortical remodeling between the cortical bone and the cancellous bone [ 15 ].…”
Section: Introductionmentioning
confidence: 99%